Bookkeeping for dummies - Kelly, Jane (Hoboken, New Jersey : John Wiley & Sons, Inc., 2015)
Learn how to "manage assets and liabilities; track business transactions accurately with ledgers and journals; prepare balance sheets, income statements, tax forms, payroll and more"--Cover.
Basic bookkeeping: why you need it. So you want to do the books -- Getting down to bookkeeping basics -- Outlining your financial road map with a chart of accounts -- Keeping a paper trail. Ledgers: a one-stop summary of your business transactions -- Keeping journals -- Computer options for your bookkeeping -- Controlling your books, your records, and your money -- Tracking your day-to-day operations with your books. Buying and tracking your purchases -- Counting your sales -- Employee payroll and benefits -- Employer-paid taxes and government payroll reporting -- Preparing the books for year's (or month's) end. Depreciating your assets -- Paying and collecting interest -- Proving out the cash -- Closing the journals -- Checking your accuracy--by trial and hopefully no error -- Adjusting the books -- Reporting results and starting over. Developing a balance sheet -- Producing an income statement -- Completing year-end payroll and reports -- Satisfying the tax man -- Prepping the books for a new accounting cycle -- The part of tens. Top ten ways to manage your business cash with your books -- Top ten most important accounts for any bookkeeper.
Includes index.
Keywords: Bookkeeping -- Handbooks, manuals, etc; Bookkeeping; Business; Bookkeeping -- Handbooks, manuals, etc; Bookkeeping; Business; Bookkeeping; Handbooks, manuals, etc